Chronic toxicity of aluminum, at a pH of 6, to freshwater organisms: Empirical data for the development of international regulatory standards/criteria. (28th December 2017) - Cardwell, Allison S.; Adams, William J.; Gensemer, Robert W.; Nordheim, Eirik; Santore, Robert C.; Ryan, Adam C.; Stubblefield, William A.
Abstract: The chemistry, bioavailability, and toxicity of aluminum (Al) in the aquatic environment are complex and affected by a wide range of water quality characteristics (including pH, hardness, and dissolved organic carbon). Data gaps in Al ecotoxicology exist for pH ranges representative of natural surface waters (pH 6–8). To address these gaps, a series of chronic toxicity tests were performed at pH 6 with 8 freshwater species, including 2 fish ( Pimephales promelas and Danio rerio ), an oligochaete ( Aeolosoma sp.), a rotifer ( Brachionus calyciflorus ), a snail ( Lymnaea stagnalis ), an amphipod ( Hyalella azteca ), a midge ( Chironomus riparius ), and an aquatic plant ( Lemna minor ). The 10% effect concentrations (EC10s) ranged from 98 μg total Al/L for D. rerio to 2175 μg total Al/L for L. minor . From these data and additional published data, species‐sensitivity distributions (SSDs) were developed to derive concentrations protective of 95% of tested species (i.e., 50% lower confidence limit of a 5th percentile hazard concentration [HC5‐50]). A generic HC5‐50 (not adjusted for bioavailability) of 74.4 μg total Al/L was estimated using the SSD. An Al‐specific biotic ligand model (BLM) was used to develop SSDs normalized for bioavailability based on site‐specific water quality characteristics. Normalized HC5‐50s ranged from 93.7 to 534 μg total Al/L for waters representing a range of European ecoregions, whereas a chronic HC5 calculated using US Environmental Protection Agency aquatic life criteria methods (i.e., a continuous criterion concentration [CCC]) was 125 μg total Al/L when normalized to Lake Superior water in the United States. The HC5‐50 and CCC values for site‐specific waters other than those in the present study can be obtained using the Al BLM. Environ Toxicol Chem 2018;37:36–48. © 2017 SETAC